Investigation of chemical spoilage in canned food in metal and plastic cans in Basrah city, Iraq (Texas Journal of Agriculture and Biological Sciences, 2023)
Food spoilage is one of the problems that cause great economic loss in most countries. This is due to storage and transportation conditions and the date of production, which requires investigating the causes of the resulting chemical spoilage and finding appropriate solutions. Fungi and bacteria may cause great damage to canned food, which may become dusty from the outer shape of metal and plastic cans and cause swelling or leakage of part of the food, and here it is necessary to focus on periodic examination of canned foods in a large way